Comparative analysis of methods for estimation of signals arrival direction - Москалец, Н.В. (Radiotekhnika, 2017)
Six methods are considered in the analysis of the methods for angular superresolution of the signals: non-adaptive beamforming, Kapon, thermal noise, Borgiotti-Lagunas, maximal entropy and multiple signal classification (MUSIC). The comparative characteristic of the methods with assessing their advantages, disadvantages and limitations is given. Theoretical resolution of these methods is assessed. The presented analysis and obtained research results make it possible to select the most effective method for determining the arrival of signals in accordance with the given parameters of signal-to-noise ratio under restrictions.